Quinone Quest: Unraveling electrochemical performance in quinone-anchored 3D graphene architectures for high-energy supercapacitors - Karaman, Ceren (2025)
In the pursuit of advancing energy storage technologies, the exploration of novel electrode materials for supercapacitors, specifically organic materials, has garnered significant attention. This work delves into the electrochemical performance of quinone-anchored three-dimensional (3D) graphene (3DG) architectures as potential electrode materials for high-energy supercapacitors, focusing on elucidating the influence of different quinone types including 1,4-naphthoquinone (NQ), anthraquinone (AQ), duraquinone (DQ), p-benzoquinone (BQ), 2,5-dimethyl-1,4-benzoquinone (DMBQ), and sodium anthraquinone-2-sulfonate (SAQS). To that end, various quinone-anchored three-dimensional graphene (Q_3DG) architectures were synthesized via a chemical reduction-induced self-assembly technique in the presence of l-ascorbic acid, a green reducing agent. The physicochemical characterizations confirmed the successful incorporation of quinones to the carbon structure, without the presence of any impurities. Different interaction mechanisms between graphene oxide (GO) and quinone molecules during the synthesis led to different surface morphologies, which affected their electrochemical behavior. The 3-electrode electrochemical characterizations in 1.0 M Na2SO4 electrolyte revealed that all Q_3DG structures exhibited superior electrochemical performance compared to GO, as well as to a Bare_3DG sample synthesized without quinone molecules. NQ anchored 3DG (NQ_3DG) network yielded the highest specific capacitance value of 386.3 F.g−1 at 10 mV.s−1, which was almost 50 times larger than that of Bare_3DG. The findings not only shed light on the fundamental mechanisms governing charge storage and transfer within these unique architectures but also provide valuable insights for the rational and green design of next-generation organic electrode-based supercapacitors with enhanced energy storage capabilities.